Digital Technologies in Kazakhstan Mass Media - Kozhakhmetova Л.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The transformation of journalism is influenced by digitalization, that is, the technological factor and the emergence of the global Internet. The emergence of a new communication channel has led to changes in the function of journalism. Technological innovation in mass communication has also influenced the social function of journalism. New technologies have become a mechanism that has consistently raised not only the media, but also Kazakhstan’s society to a new level. However, the impact of new communication technologies is not one-sided. The conflict of new and traditional means has shaped a new approach to the values of journalism. The impact of changes in the digital age is much deeper than the previous journalism, based on material, clothing transportation. Unlike previous technological revolutions, the transition of truth to the virtual world is interactive and global. To date, not only the methods of dissemination of information, but also the environment of its users have changed. Kazakhstan journalism, adapted to the new conditions, experiments any kind of information dissemination. The article analyzes the novelty of digital technologies, given in the Kazakh press, the assessment to date.